Reframing “Harmony”: Humans as Functional Components in British Romantic Pastoral Ecosystems - Kopp, Marissa; Webster, Suzanne (Romanticism on the Net)

(untitled) (Université de Montréal, 2024)
COVID-quarantine narratives of human–nonhuman “harmony” often emphasised environmental benefits of human absence from landscapes. However, nowadays, even “in lockdown,” humans affect all Earthly ecosystems. Consequently, ecocritics frequently deem depictions of “positive human absence” unhelpful to current eco-crises, “pastoral literature” being one of their main offenders. What these respective positions discount, though, is that some ecosystems depend upon human functional roles—including the semi-natural grasslands of “ecological pastoral” systems, which can suffer a variety of problematic ecological consequences upon the withdrawal of human activity. Accordingly (we propose), truly pastoral literature frames human–nonhuman harmony in terms not of “positive human absence,” but, rather, of “positive human presence,” “negative human presence,” and “negative human absence.” Via historico-cultural explorations of poetry’s millennia-spanning ecological roles, of humans’ developing knowledge about grasslands, and of British land-management (re)arrangements circa 1750–1860, we forge an innovative ecological-pastoral interpretative lens, which we then apply to poems by Oliver Goldsmith, John Clare, and (to a lesser extent) William Wordsworth. The resulting readings show how, if viewed through an ecological-pastoral lens, the “literary pastoral” could, in fact, help tackle Anthropocenic environmental crises by (re)educating humans about their integral, rather than dominant, ecological roles on Earth.This paper contains four sections. First, the Prologue explores some reasons why pastoral poetry is often dismissed by ecocritics but embraced by disseminators of both traditional and scientific ecological knowledge. This exploration is conducted through considerations of “the pastoral,” “the georgic,” the nature of poetic expression, and poetry’s “ecological worth.” In the next section, “Ecological-Pastoral: The Theory,” we use recent research on grassland biomes and climate change to create an ecologically based interpretative lens through which to consider “the pastoral” within the context of literary works—an approach differing markedly from already-existing ecocritical techniques. Moving to the “Ecological-Pastoral in Practice,” current knowledge about grasslands and pastoral ecosystems is compared with eighteenth- and nineteenth-century knowledge; and our new interpretative lens is used to analyse several pastoral poems of 1770–1840. Finally, in the Epilogue, we introduce our “companion article,” which illustrates further how our interpretative framework can enable and encourage people to value historical literary works as relevant, useful tools in the context of tackling Earth’s current environmental emergencies.